Geostrategic Visions on the South Atlantic: Brazil and Colombia, a Comparative Approach - Gisela da Silva Guevara (Revista Mexicana de Ciencias Políticas y Sociales)
This article seeks to analyze the different approaches that Brazil and Colombia have had to date on the geostrategic importance of the South Atlantic, emphasizing the differences that the ocean has had for its respective conception of country and its insertion in the South American region. For these purposes I focus on three variables; development, defense and regional security, in order to assess the importance of the South Atlantic and the influence in these two nations’ strategic environment. I argue and conclude that while Brazil seeks leadership in South America through an emphasis on its role as promoter of an integral autonomizing conception for the South Atlantic that articulates development, defense and regional security, Colombia in turn prioritizes its role in the region as a reference in the fight against transnational crime, positioning itself as a Middle Oceanic Power.